Synovial chondromatosis of temporomandibular joint spreading into the cranial space. Issue 3 (May 2018) - Romano, Antonio; Lo Faro, Carmelo; Salzano, Giovanni; Dell'aversana Orabona, Giovanni; Petrocelli, Marzia; Corvino, Raffaele; Vaira, Luigi Angelo; Iaconetta, Giorgio; Califano, Luigi
Abstract: Synovial Chondromatosis (SC) of the upper temporomandibular joint (TMJ) compartment spreading into the cranial space is a very rare condition and only 13 cases are described in Literature. The case of a 45-year-old woman with a slight swelling of the right TMJ and opening clicking is presented in this report. Patient orthopantomography showed large calcified masses in the right TMJ space. CT scan and MRI confirmed this finding showing granular masses surrounding the right condylar head spreading into the middle cranial fossa. After biopsy, the lesion was diagnosed as SC, and radical surgical excision was performed. A good functional recovery with no signs of recurrence at 18 months of follow-up was obtained with a good cosmetic result. An extensive review of the literature has been performed and the results are presented in order to establish a correct diagnostic-therapeutic protocol for these oncologic patients.